Re-planning the Layout of Production Facilities Using the Method Activity Realition Chart (ARC) At PT. Betts Indonesia Perencanaan Ulang Tata Letak Fasilitas Produksi Dengan Menggunakan Metode Activity Realition Chart (ARC) Di PT. Betts Indonesia - Putra, Boy Isma Putra; Putra, Fransiscus Pradana Chrisanto (2477 - 6165, 2023)
PT. Betts Indonesia is a manufacturing company that produces laminate tubes. In the production process, several materials used in the production process to become finished products. The problems found in this study are the irregularity of the layout of production materials, often the placement of materials that are not in accordance with the material specifiedFor the flow of raw materials, bottlenecks often occur because the existing lines are narrow, so they have to alternate with each other, which causes a decrease in the efficiency of the production process. The method in this study uses the Activity Realition chartto improve the material flow that has been carried out currently with the aim of rearranging the layout of efficient production facilities so as to optimize material handling. From the results of this study it is expected to rearrange the flow of raw materials more efficiently so that the level of the production process can produce the maximum production process from the targets set by the company.